Particle Scale Numerical Simulation on Momentum and Heat Transfer of Two Tandem Spheroids: An IB-LBM Study (Advances in Applied Mathematics and Mechanics, 2021)
The cold fluid flowing over two hot spheroids placed in a tandem arrangementwas numerically studied via a GPU-based immersed boundary-lattice Boltzmannmethod (IB-LBM) model. The drag coefficient and average Nusselt number ofboth the two spheroids were obtained with the main influencing factors investigated.To validate the IB-LBM model, several numerical case studies containing one and twospheres were firstly conducted to reach the good agreement with the previously reporteddata. Then, a number of simulations were further carried out which were designedby changing the particle aspect ratio (1.0≤ $Ar$ ≤4.0) and inter particle distance(1.5≤ $l$ ≤7.0, where $l = L/D$, $D$ stands for the volume-equivalent sphere diameter) aswell as the Reynolds number (10 ≤ $Re$ ≤200). Their influence on the momentum andheat transfer characteristics between the solid and fluid phases were fully discussed.Numerical results show that, for all the considered Reynolds numbers and aspect ratios,the individual and total drag coefficients and average Nusselt number increasewith the inter particle distance. The inter particle distance has greater influence on thedrag coefficient and average Nusselt number of the trailing particle than the leadingone. The drag coefficient and average Nusselt number of the trailing particle are farless than the leading one under the same working conditions. The prediction correlationsfor the drag coefficient and average Nusselt number of both the two spheroidswere established with low deviations. At last, the influence of the relative incidenceangles between the two tandem spheroids on the momentum and heat transfer wasstudied. It is shown that the relative incidence angles play significant roles due to thechange of the frontal area of the leading spheroid with these angles.